Barriers to family history collection among Spanish-speaking primary care patients: a BRIDGE qualitative study - Erica Liebermann; Peter Taber; Alexis S. Vega; Brianne M. Daly; Melody S. Goodman; Richard Bradshaw; Priscilla A. Chan; Daniel Chavez-Yenter; Rachel Hess; Cecilia Kessler; Wendy Kohlmann; Sara Low; et al. (Elsevier, 2022)
Objectives: Family history is an important tool for assessing disease risk, and tailoring recommendations for screening and genetic services referral. This study explored barriers to family history collection with Spanish-speaking patients. Methods: This qualitative study was conducted in two US healthcare systems. We conducted semi-structured interviews with medical assistants, physicians, and interpreters with experience collecting family history for Spanish-speaking patients. Results: The most common patient-level barrier was the perception that some Spanish-speaking patients had limited knowledge of family history. Interpersonal communication barriers related to dialectical differences and decisions about using formal interpreters vs. Spanish-speaking staff. Organizational barriers included time pressures related to using interpreters, and ad hoc workflow adaptations for Spanish-speaking patients that might leave gaps in family history collection. Conclusions: This study identified multi-level barriers to family history collection with Spanish-speaking patients in primary care. Findings suggest that a key priority to enhance communication would be to standardize processes for working with interpreters. Innovation: To improve communication with and care provided to Spanish-speaking patients, there is a need to increase healthcare provider awareness about implicit bias, to address ad hoc workflow adjustments within practice settings, to evaluate the need for professional interpreter services, and to improve digital tools to facilitate family history collection.